Peningkatan Kemampuan Ibu-Ibu Desa Stabat Lama, Kabupaten Langkat - Fahmi Sulaiman; Jihan Sulaiman; Neni Triastuti; ZUBAIDAH Hanum; Flora Elisabeth Silalahi (Jurnal Masyarakat Indonesia (Jumas), 2024)
The World Health Organization (WHO) stated that the world is entering a global emergency regarding this virus. Many countries in the world are affected, including Indonesia. The outbreak of this virus has resulted in the economy in Indonesia being paralyzed because many small, micro and medium businesses cannot survive and have closed all their production activities, resulting in layoffs. The absence of production activities and termination of employment results in the loss of sources of funds obtained to carry out life in a family. This is proven based on data from the Ministry of Religion of the Republic of Indonesia that the divorce rate increased during the Covid-19 pandemic, which was caused by the family's economic situation. It is time, as a housewife, to understand the concept of family financial management well so that every family is able to face difficult times like this and is able to maintain the welfare of their family. There are several objectives of this PKM, namely a) Increasing Knowledge regarding Financial Management Concepts, b) Housewives can identify Needs and Desires, c) Housewives can make a household budget and evaluate the family's financial health, d) Every Family can afford increase Cash In and reduce Cash Out. PKM has the following stages: a) Discussion stage, this stage is carried out by the PKM team to explain the concept of financial management b) Workshop stage, which is carried out directly in the financial management training process